Resin composition for laser welding cylindrical molded body, laser welding cylindrical molded body using the same, and cylindrical molded body-tube bonded structure

JP7641735B2Active Publication Date: 2025-03-07SUMITOMO RIKO CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020216909
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-25
Publication Date
2025-03-07
Estimated Expiration
2040-12-25

AI Technical Summary

Benefits of technology

【0012】 以上のことから、本発明のレーザー溶着用筒状成形体用樹脂組成物は、高温強度等の改善がなされるとともに、自動車用チューブ用のコネクタのような筒状成形体となるよう射出成形する際に顕著に生じるウェルド部に、ガラス繊維フィラーが凝集するのを低減することができ、上記筒状成形体をレーザー溶着する際の溶着性を改善することができる。そのため、上記樹脂組成物を用いたレーザー溶着用筒状成形体も、高いレーザー溶着性等を示す。そして、上記レーザー溶着用筒状成形体とチューブとがレーザー溶着されてなる結合構造体(筒状成形体-チューブ結合構造体)も、その結合部分(溶着部全周)の溶着強度が向上するため、チューブを流れる流体の漏れや、チューブが筒状成形体から外れるなどの問題を解消することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641735000002
    Figure 0007641735000002
  • Figure 0007641735000001
    Figure 0007641735000001
Patent Text Reader

Abstract

To provide a resin composition for a cylindrical molding for laser beam welding which can improve weldability when a cylindrical molding such as a connector for a tube for an automobile is welded by a laser beam, a cylindrical molding for laser beam welding using the same, and a bond structure obtained by welding the cylindrical molding for laser beam welding and a tube by a laser beam.SOLUTION: A resin composition for a cylindrical molding for laser beam welding contains the following components (A) to (C) in a specific ratio as a material of a connector 1 welded to a resin tube 2 by a laser beam. (A) At least one selected from the group consisting of polypropylene and polyamide (excluding (C)). (B) Glass fiber filler having a refractive index whose difference with the refractive index of (A) is 0.02 or less. (C) Compatibilizer having the same constitutional unit as the main chain of (A), and having a functional group showing reactivity to a hydroxyl group of the surface of (B) the glass fiber filler.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition for a tubular molded body for laser welding, a tubular molded body for laser welding using the same, and a bonded structure (tubular molded body-tube bonded structure) formed by laser welding the tubular molded body for laser welding and a tube. [Background technology]

[0002] Conventionally, a method of fastening an automotive tube to a connector is used in which the automotive tube is press-fitted into a connector equipped with an O-ring to ensure a seal. However, this fastening method requires an increased number of parts, such as sealing parts like O-rings, which increases the number of assembly steps and increases costs.

[0003] In recent years, welding fastening has been attracting attention as a fastening method to replace the press-fit fastening using the above-mentioned sealing parts. Among the welding fastening techniques for cylindrical components such as connectors that connect tubes, spin welding (welding using frictional heat caused by rotation) is known to be advantageous in that welding can be done with inexpensive equipment. However, spin welding has a problem in that the welded portion is prone to contamination due to the generation of burrs. Laser welding has therefore attracted attention as a method for solving the above-mentioned problem of contamination of the welded portion.

[0004] Laser welding is a technique in which laser light that has passed through a laser-transmitting material is absorbed by the laser-absorbing material, generating heat, melting the laser-absorbing material and melting the laser-transmitting material through heat transfer, thereby welding a laser-transmitting material to a laser-absorbing material. The welding condition by the above-mentioned laser welding changes depending on the laser energy transmitted to the absorbing material, and is affected by the laser light output, the laser light transmittance of the transmitting material, the thickness of the transmitting material, etc. If the laser light energy is too low, welding failure occurs, and if the laser light energy is too high, welding failure occurs due to material degradation. For this reason, in laser welding, it is required to suppress variations in the transmittance of the laser transmitting material and to make the energy of the laser light transmitted to the laser absorbing material constant.

[0005] Here, for example, Patent Document 1 discloses a laser transparent material specialized for the above-mentioned laser welding. In Patent Document 1, a polypropylene molded body is used as a laser transmitting material, and the polypropylene molded body contains an inorganic filler having a refractive index similar to that of polypropylene in order to improve the mechanical strength of the polypropylene molded body without impeding the transmission of laser light (laser welding performance). Examples using talc and white mica as the inorganic filler are shown. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2005-001350 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, Patent Document 1 does not fully address the problem of filler aggregation caused by the occurrence of welds, which is prominent when producing cylindrical molded products such as connectors for automobile tubes.

[0008] That is, in the embodiment of Patent Document 1, the sheet material is manufactured by injection molding, but in the manufacture of such sheet material, the flow direction of the resin by injection molding is usually unidirectional, so that welds are hardly generated and the aggregation of the filler as described above hardly becomes a problem. However, when producing a cylindrical molded article, the resin flows in many directions, and welds occur significantly at the joining points, where the filler tends to aggregate significantly. In addition, if the filler is one such as that used in the examples of Patent Document 1 (talc, white mica), sufficient strength (especially high-temperature strength) cannot be obtained when the connector is molded, so for example, the use of a filler made of glass fiber has been considered, but the glass fiber generally available on the market (glass fiber made of E glass, etc.) has a higher refractive index than, for example, polypropylene. Therefore, there is a problem that the laser light is easily reflected at the interface between the matrix polymer and the glass fiber, resulting in a decrease in the laser transmittance and a decrease in the amount of energy of the laser light transmitted to the laser absorbing material. In view of this, the use of glass fibers having a refractive index close to that of polypropylene has been considered. However, even in this case, when the laser light hits the aggregated parts of the glass fibers, the laser light is scattered, which causes a problem that good laser welding cannot be performed. Therefore, even if the laser-transmitting material disclosed in Patent Document 1 is a tubular molded body such as a connector for automobile tubes, and glass fiber is used as a filler, and the end of a resin tube is inserted into the open edge of the tubular molded body and laser welded, it is not possible to sufficiently weld the connector and the tube (the weld strength cannot be ensured around the entire circumference of the welded part), which may result in problems such as leakage of the fluid flowing through the resin tube or the resin tube becoming detached from the tubular molded body.

[0009] The present invention has been made in consideration of the above circumstances, and has an object to provide a resin composition for tubular molded bodies for laser welding, which can improve the weldability, etc., when laser welding tubular molded bodies such as connectors for automobile tubes, a tubular molded body for laser welding using the same, and a bonded structure (tubular molded body-tube bonded structure) formed by laser welding the above-mentioned tubular molded body for laser welding and a tube. [Means for solving the problem]

[0010] The present inventors have conducted intensive research to solve the above problems. In the course of the research, they came up with the idea of ​​using at least one (A) selected from the group consisting of polypropylene and polyamide as the base polymer for the material of the cylindrical molded body as described above, and containing a glass fiber filler (B) that has a refractive index that is within 0.02 different from the refractive index of the base polymer, and a compatibilizer (C) that has the same structural unit as the main chain of the base polymer and has a functional group that is reactive to the hydroxyl group on the surface of the glass fiber filler (B) in the material. As a result, the laser light is transmitted without being scattered at the interface of the glass fiber filler, and the dispersibility of the glass fiber filler (B) is improved, so that the aggregation of the glass fiber filler (B) in the weld portion during injection molding of the cylindrical molded body can be reduced. From these findings, they have found that it is possible to improve the weldability during laser welding, and have arrived at the present invention.

[0011] That is, in order to achieve the above object, the present invention provides the following [1] to [8]. [1] A resin composition for use in a cylindrical molding for laser welding, comprising the following components (B) and (C) together with a base polymer made of the following component (A), wherein the weight ratio of components (B) and (C) is (B):(C)=2:0.01 to 2:1. (A) At least one selected from the group consisting of polypropylene and polyamide (excluding (C)). (B) A glass fiber filler having a refractive index that differs from the refractive index of (A) by 0.02 or less. (C) A compatibilizer having the same structural unit as the main chain of (A) above and having a functional group that is reactive with the hydroxyl group on the surface of the glass fiber filler (B) above. [2] The resin composition for use in a cylindrical molding for laser welding according to [1], wherein the component (A) is polypropylene and the component (C) is maleic anhydride-modified polypropylene. [3] The resin composition for use in a cylindrically shaped body for laser welding according to [2], wherein the maleic anhydride-modified polypropylene has a maleic anhydride modification rate of 0.1 to 4.0 mol %. [4] The above-mentioned (A) component is a polyamide, and the above-mentioned (C) component has a melt volume rate (MVR) of 1 to 200 cm3 measured at a measurement temperature of 180°C and a load of 2.16 kg. 3 The resin composition for use in a cylindrical molding for laser welding according to [1], which is a polyamide having a thickness of 1 / 10 mm. [5] The resin composition for use in a tubular molding for laser welding according to any one of [1] to [4], wherein the content of the component (B) relative to the total content of the components (A) to (C) is 2.0 to 50% by weight. [6] A cylindrically shaped body for laser welding, comprising the resin composition for use in a cylindrically shaped body for laser welding according to any one of [1] to [5]. [7] The cylindrical molded article for laser welding according to [6], which is a connector for tubes in an automobile. [8] A cylindrical molding-tube bonded structure, characterized in that the end of a resin tube is inserted into the open end edge of the laser welding cylindrical molding described in [6] or [7] and laser welded to it. Effect of the Invention

[0012] From the above, the resin composition for a cylindrical molded body for laser welding of the present invention has improved high-temperature strength and the like, and can reduce the aggregation of glass fiber filler at the weld portion that occurs significantly when injection molding is performed to form a cylindrical molded body such as a connector for an automobile tube, and can improve the weldability when the cylindrical molded body is laser welded. Therefore, a cylindrical molded body for laser welding using the resin composition also exhibits high laser weldability and the like. And, the weld strength of the joint portion (whole circumference of the welded portion) of the joint structure (cylindrical molded body-tube joint structure) formed by laser welding the cylindrical molded body for laser welding and the tube is also improved, so that problems such as leakage of the fluid flowing through the tube and the tube coming off the cylindrical molded body can be solved. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a cylindrical molded body-tube connection structure of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Next, an embodiment of the present invention will be described in detail, although the present invention is not limited to this embodiment.

[0015] As described above, the resin composition for tubular moldings for laser welding of the present invention contains the following components (B) and (C) together with a base polymer consisting of the following component (A), and the weight ratio of components (B) and (C) is (B):(C)=2:0.01 to 2:1. (A) At least one selected from the group consisting of polypropylene and polyamide (excluding (C)). (B) A glass fiber filler having a refractive index that differs from the refractive index of (A) by 0.02 or less. (C) A compatibilizer having the same structural unit as the main chain of (A) above and having a functional group that is reactive with the hydroxyl group on the surface of the glass fiber filler (B) above. In the present invention, the refractive index refers to the refractive index for a laser beam of 1060 nm, and was determined by creating an approximation curve from d-line (587.6 nm), e-line (546.1 nm), and t-line (1013.98 nm) using a precision refractometer KPR-3000 to determine the refractive index at 1060 nm. Therefore, the refractive index of each material described below was determined by this method.

[0016] Each material of the resin composition will be described in detail below.

[0017] [Component (A)] The base polymer (A) of the resin composition is at least one selected from the group consisting of polypropylene and polyamide (excluding the later-described (C) component). In the present invention, the base polymer has a large effect on the properties of the resin composition, and usually accounts for 45% by weight or more of the total of the (A) to (C) components, and preferably 45% by weight or more of the entire resin composition.

[0018] The polypropylene is preferably, for example, a homopolymer of propylene (homopolypropylene), but may also be a copolymer with other olefin monomers such as ethylene, or other monomers such as (meth)acrylic acid esters, except for modified polypropylenes such as maleic anhydride modified polypropylene. The polypropylene generally has a melt flow rate (MFR) of 0.1 to 50 g / 10 min, measured at a temperature of 190° C. and a load of 2.16 kg according to JIS K 7210. The melt flow rate (MFR) is preferably 0.5 to 45 g / 10 min, more preferably 1 to 40 g / 10 min, and even more preferably 2 to 35 g / 10 min. The MFR can be measured using a melt indexer. The polypropylene generally has a refractive index of 1.470 to 1.510. The refractive index is preferably 1.475 to 1.505, more preferably 1.480 to 1.500, and even more preferably 1.485 to 1.495.

[0019] In addition, the polyamide may be, for example, polyamide 6, polyamide 46, polyamide 66, polyamide 610, polyamide 612, polyamide 11, polyamide 12, polyamide 92, polyamide 99, polyamide 912, polyamide 1010, polyamide 6I, polyamide 6T, polyamide 9T, polyamide 10T, polyamide 11T, polyamide MXD6, polyamide 6T / 6I, polyamide 6 / 6I, polyamide 66 / 6T, polyamide 66 / 6I, or a polyamide copolymer containing at least two different structural components among the polyamide components constituting these polyamides. These may be used alone or in combination of two or more. Among them, polyamide 12 is preferred because it has excellent calcium chloride resistance and can suppress cracks caused by adhesion to snow-melting agents (calcium chloride resistance). The polyamide generally has an MVR (in the case of an aliphatic polyamide, the melt volume rate (MVR) is measured in accordance with JIS K 7210 at a measurement temperature of 275° C. and a load of 5 kg; in the case of an aromatic polyamide, the melt volume rate (MVR) is measured in accordance with JIS K 7210 at a measurement temperature of 325° C. and a load of 2.16 kg) of 0.1 to 40 cm 3 The MVR is preferably 0.2 to 38 cm 3 / 10 minutes, preferably 0.3 to 35 cm 3 / 10 minutes, more preferably 0.4 to 30 cm 3 The melt volume rate (MVR) of the above polyamide, measured in accordance with JIS K 7210 at a measurement temperature of 180°C and a load of 2.16 kg, is 0.1 cm 3 / 10 minutes or less (high molecular weight), it is different from the component (C) described later. The above MVR can be measured using a melt indexer. The polyamide used generally has a refractive index of 1.51 to 1.55. The refractive index is preferably 1.515 to 1.545, more preferably 1.52 to 1.54, and even more preferably 1.525 to 1.535.

[0020] [(B) Component] The component (B) is a glass fiber filler having a refractive index that is within 0.02 different from the refractive index of the base polymer (component (A)) of the resin composition. The difference in refractive index is preferably within 0.01, more preferably 0. As described above, the glass fiber filler (B) to be used (glass fiber filler having a refractive index difference within the above range) is determined by the selection (refractive index) of the matrix polymer, which is component (A). The refractive index of the glass fiber filler is preferably 1.4 to 1.7, more preferably 1.44 to 1.64, and even more preferably 1.48 to 1.58.

[0021] The glass fibers that are the material of the glass fiber filler (B) include filamentous fibers obtained by melt spinning glass such as D glass (low dielectric constant glass), NE glass (low dielectric constant non-alkali glass), E glass (non-alkali glass), C glass (acid-resistant alkali glass), A glass (alkali glass), S glass (high strength and high elasticity glass), and alkali-resistant glass. Among these, D glass and NE glass are preferably used because they have a small difference in refractive index from the matrix polymer that is the component (A). Furthermore, the fiber diameter of the glass fibers is preferably 2.5 to 20 μm, more preferably 5 to 15 μm, from the viewpoints of injection molding processability and laser light transmittance.

[0022] From the viewpoint of improving the high-temperature strength of the cylindrical molded body, the content of the (B) component in the resin composition relative to the total (100% by weight) of the (A) to (C) components is preferably in the range of 2.0 to 50% by weight, more preferably 10 to 30% by weight, and even more preferably 15 to 25% by weight.

[0023] [(C) component] For component (C), a compatibilizer is used which has the same structural units as the main chain of the base polymer (component (A)) of the resin composition and has a functional group (such as a carboxylic acid group, an anhydride of a carboxylic acid group, an epoxy group, or an amide group) that is reactive with the hydroxyl group on the surface of the glass fiber filler (B). As described above, the compatibilizer to be used is determined by the main chain of the base polymer, which is component (A). When polypropylene and polyamide are used in combination as component (A), a compatibilizer having the same structural unit as either of the main chains may be used.

[0024] When the component (A) is polypropylene, the compatibilizer (C) may be maleic anhydride-modified polypropylene, imine-modified polypropylene, etc., which may be used alone or in combination. Among these, from the viewpoint of improving the laser weldability of the cylindrical molded body, maleic anhydride-modified polypropylene is preferred, more preferably polypropylene having a maleic anhydride modification rate of 0.01 to 20 mol%, even more preferably polypropylene having a maleic anhydride modification rate of 0.05 to 10 mol%, and particularly preferably polypropylene having a maleic anhydride modification rate of 0.1 to 5 mol%. When the compatibilizer (C) is maleic anhydride-modified polypropylene or the like as described above, the melt flow rate (MFR) of the compatibilizer (C) measured at a measurement temperature of 190° C. and a load of 2.16 kg in accordance with JIS K 7210 is preferably 0.1 to 400 g / 10 min, more preferably 0.3 to 300 g / 10 min, and even more preferably 0.1 to 200 g / 10 min. The MFR can be measured using a melt indexer. Furthermore, when the compatibilizer (C) is maleic anhydride modified polypropylene or the like as described above, the refractive index of the compatibilizer (C) is preferably 1.475 to 1.505, more preferably 1.480 to 1.500, and further preferably 1.485 to 1.495. As described above, when component (A) is polypropylene and compatibilizer (C) is maleic anhydride-modified polypropylene, the maleic anhydride groups of the compatibilizer (C) react with and bond to the hydroxyl groups on the surface of the glass fiber filler (B), and the polypropylene part of the compatibilizer (C) has excellent compatibility with the base polymer, improving dispersibility. As a result, the laser light transmittance and high-temperature strength of the cylindrical molded product are also improved.

[0025] When the component (A) is a polyamide, the compatibilizer (C) is a polyamide having a melt volume rate (MVR) of 1 to 200 cm as measured at a temperature of 180° C. and a load of 2.16 kg according to JIS K 7210. 3In particular, from the viewpoint of improving the laser weldability of the cylindrical molded body, the MVR is preferably 2 to 175 cm 3 / 10 minutes, preferably 3 to 150 cm 3 / 10 minutes, more preferably 4 to 125 cm 3 / 10 min, preferably 5 to 100 cm 3 The MVR can be measured using a melt indexer. The above-mentioned low molecular weight polyamide is obtained from an excess of polyamine and polybasic acid. In addition, as described above, when component (A) is a polyamide and the compatibilizer (C) is a polyamide (low molecular weight polyamide) exhibiting the above MVR, the addition of the low molecular weight polyamide increases the amount of terminal amides, improving the reactivity with the hydroxyl groups on the surface of the glass fiber filler (B). The low molecular weight polyamide has excellent compatibility with the matrix polymer, preventing re-aggregation of the glass fiber filler (B) and improving dispersibility. As a result, the laser light transmittance and high temperature strength of the cylindrical molded product are also improved. Furthermore, when the compatibilizer (C) is a low molecular weight polyamide as described above, the refractive index of the compatibilizer (C) is preferably 1.515 to 1.545, more preferably 1.52 to 1.54, and further preferably 1.525 to 1.535.

[0026] From the viewpoint of improving the laser weldability of the cylindrical molded body, the weight ratio of the components (B) and (C) in the resin composition is in the range of (B):(C)=2:0.01 to 2:1, preferably (B):(C)=2:0.02 to 2:0.5, and more preferably (B):(C)=2:0.1 to 2:0.3.

[0027] [Other ingredients] In addition to the above-mentioned components, the resin composition for tubular moldings for laser welding of the present invention may contain other components, such as colorants (dyes and pigments), heat stabilizers, antioxidants, inorganic fillers, crystal nucleating agents, weather resistance agents, plasticizers, lubricants, impact resistance materials, etc., as necessary, within the types and ranges that do not impair the laser light transmittance.

[0028] Examples of the dye include azo-, anthraquinone-, perinone-, perylene-, phthalocyanine-, carbonium-, and indigoid-based oil dyes, acid dyes, basic dyes, and disperse dyes. Among these, perylene-based dyes are preferred because of their excellent laser transmittance.

[0029] Examples of the pigment include organic pigments such as phthalocyanine-based, anthraquinone-based, isoindolinone-based, quinacridone-based, perylene-based, azo-based, etc. Among them, perylene-based organic pigments are preferred because of their excellent laser transmittance.

[0030] As described above, since the colorant needs to be used in an amount that does not impair the laser beam transmittance, the content of the colorant in the resin composition for a cylindrical molded body for laser welding of the present invention is usually less than 1% by weight. From the above viewpoint, the content of the colorant is preferably less than 0.75% by weight, more preferably less than 0.5% by weight.

[0031] <Method of manufacturing cylindrical molded body for laser welding> Next, the cylindrical molded article for laser welding of the present invention is produced, for example, as follows.

[0032] That is, first, the base polymer (A), glass fiber (glass fiber filler (B)), compatibilizer (C), and other components, if necessary, are melt-kneaded using a twin-screw extruder at a cylinder temperature of 200 to 260° C. Then, pellets are obtained from the above melt-kneaded product (the resin composition for a cylindrical molded body for laser welding of the present invention). Next, the pellets are injection molded in a mold for a cylindrically molded body by an injection molding machine at a set temperature of 200 to 280° C. In this manner, the desired cylindrically molded body can be produced.

[0033] As another manufacturing method, the base polymer (A), glass fiber (glass fiber filler (B)), compatibilizer (C), and other components, as necessary, may be directly fed into an injection molding machine in the required amounts for each shot, and the desired tubular molded body for laser welding may be obtained by injection molding. Furthermore, after a portion of each of the above materials is mixed in advance, the mixture is directly fed into an injection molding machine together with the remaining materials in the required amounts for each shot, and the desired tubular molded body for laser welding is obtained by injection molding.

[0034] The fiber length of the glass fibers used in the above-mentioned various manufacturing methods is usually 2 to 6 mm, and preferably 3 to 5 mm. Note that, since the glass fibers are broken in a melt kneader or an injection molding machine and become finer, the above-mentioned fiber length is usually different from the glass fiber length in the cylindrical molded body for laser welding.

[0035] <Cylindrical molded body for laser welding> From the viewpoint of laser weldability, the thus obtained cylindrical molded article for laser welding usually has a substantially cylindrical shape with an inner diameter of 2.5 to 50 mm, a wall thickness of 0.25 to 10 mm, and a length of 20 to 1000 mm. The inner diameter is preferably 3 to 45 mm, more preferably 3.5 to 40 mm, and even more preferably 4 to 35 mm. The wall thickness is preferably 0.5 to 7.5 mm, more preferably 0.75 to 5 mm, and even more preferably 1.0 to 3.0 mm. The length is preferably 25 to 500 mm, more preferably 30 to 250 mm, and even more preferably 35 to 100 mm. Since the cylindrical molded body for laser welding is "approximately cylindrical" as described above, it is not limited to being completely cylindrical, but may have any shape that allows laser welding with the end of a resin tube inserted into the open end edge.

[0036] When the total light transmittance at 1060 nm is measured for the cylindrical body for laser welding using a spectrophotometer (e.g., V-770 manufactured by JASCO Corporation), the total light transmittance is preferably 55% or more, more preferably 57% or more, and even more preferably 60% or more. The total light transmittance for the weld portion of the cylindrical body for laser welding is preferably 50% or more, more preferably 52% or more, and even more preferably 55% or more.

[0037] In addition, when the central portion (central portion in the longitudinal direction) of the above-mentioned tubular molding for laser welding is fixed and a JIS K 7171 indenter (tip R2.0) is pressed perpendicular to the axis into the opening at the tip of the tubular molding in a cantilever state with a length of 10 mm at a pressing speed of 5 mm / min, the breaking strength (N) is measured by compression evaluation using a tensile testing machine, Strograph, and is preferably 450 N or more, more preferably 500 N or more, even more preferably 550 N or more, and particularly preferably 600 N or more.

[0038] The thus-obtained cylindrical molded article for laser welding of the present invention is preferably used as a connector for tubes in automobiles, a connector for water pipes, etc. Among these, a connector for tubes in automobiles is more preferable.

[0039] <Cylindrical molded body-tube joint structure> FIG. 1 is a cross-sectional view showing an example of the cylindrical molded body-tube connection structure of the present invention, in which 1 is a connector (cylindrical molded body) and 2 is a resin tube. The connector 1 is the cylindrical molded body for laser welding of the present invention. As shown in the figure, in a state where an end of a resin tube 2 is inserted into an opening edge 1a of the connector 1, laser light is irradiated from the outside of the connector 1, whereby the laser light transmitted through the connector 1 is absorbed by the resin tube 2 to generate heat, and the base polymer of the resin tube 2 melts. The heat is further transferred to the connector 1, whereby the base polymer of the connector 1 also melts. In this way, the interface between the two is welded.

[0040] The connector 1 and the resin tube 2 are not normally bonded together unless their base polymers are of the same material, but it is possible to weld them together by applying a hot melt film, adhesive coating, electrostatic coating, or other surface treatment to the opening edge 1a of the connector 1 or the welding surface of the resin tube 2. In addition, the material of the resin tube 2 or the welding surface of the resin tube 2 must be made of a material that absorbs laser light and generates heat (carbon black, inorganic pigments, organic pigments, dyes, etc.). The resin tube 2 is usually long, and the length of the connector 1 is shorter than that of the resin tube 2.

[0041] The laser used in the present invention may have an oscillation wavelength of 800 to 1200 nm, and may be any of known lasers such as a YAG laser, a semiconductor laser, a glass laser, a ruby ​​laser, a He-Ne laser, a nitrogen laser, a chelate laser, a dye laser, etc. The output of these lasers is preferably about 5 to 40 W.

[0042] The laser irradiation time and the distance between the laser and the object to be irradiated (connector 1 and resin tube 2) must be adjusted taking into consideration the laser output, the thickness of connector 1, the laser transmittance of connector 1, and the like.

[0043] When the tubular molded body-tube connection structure of the present invention is produced by inserting 1.5 cm of the resin tube 2 into the open end edge of the connector 1, and while maintaining this state, irradiating a laser beam from the outside of the tubular molded body at a position 10 mm from the position where the resin tube 2 and connector 1 begin to overlap with each other at a laser output of 40 W and 1 second / cycle to weld the interface between the connector 1 and the resin tube 2, the weld strength (N) as determined by axial tensile evaluation using a Strograph tensile testing machine is preferably 450 N or more, more preferably 475 N or more, and even more preferably 500 N or more. EXAMPLES

[0044] Examples will be described below together with comparative examples. However, the present invention is not limited to these examples as long as the gist of the present invention is not exceeded.

[0045] First, cylindrical molded bodies of the examples and comparative examples were produced according to the following procedure. The refractive index of each material used in the cylindrical molded body indicates the refractive index at 1060 nm of laser light, and the refractive index at 1060 nm was calculated by creating an approximation curve from d-line (587.6 nm), e-line (546.1 nm), and t-line (1013.98 nm) using a precision refractometer KPR-3000.

[0046] [Example 1] 79.9 parts by weight of polypropylene (product name: Novatec PP MA1B, manufactured by Nippon Polypropylene Co., Ltd., refractive index: 1.49, MFR (measured in accordance with JIS K 7210 at a measurement temperature of 190°C and a load of 2.16 kg): 21 g / 10 min), 0.1 parts by weight of acid-modified polypropylene (product name: TPPP9232, manufactured by BYK Co., Ltd., maleic anhydride-modified polypropylene, maleic anhydride modification rate: 2.0 mol%, refractive index: 1.49, MFR (measured in accordance with JIS K 7210 at a measurement temperature of 190°C and a load of 2.16 kg) 6 g / 10 min), and glass fiber (GF) filler made of D glass (glass chopped strands with a fiber diameter of φ11 μm cut to a cut length of 3 mm, refractive index: 1.48, product name: ECS(HL)-301TDS, Chongqing International Composite Materials Co., Ltd. A mixture of 20 parts by weight of a colorant (product name: LUMOGEN Black K 0087, manufactured by BASF Japan) and 0.1 parts by weight of a perylene-based colorant (product name: LUMOGEN Black K 0087, manufactured by BASF Japan) was melt-kneaded in a twin-screw extruder (screw diameter: 30 mm) at a cylinder temperature of 180°C to obtain pellets. The pellets were then injection molded in a mold for a cylindrical body at a set temperature of 180° C. using an injection molding machine to produce a cylindrical body having an outer diameter of 12 mm, a wall thickness of 2 mm, and a length of 25 mm.

[0047] [Examples 2 to 4, Comparative Examples 1 to 8] The components shown in Table 1 below were mixed in the ratios shown in the same table, and pellets were prepared in the same manner as in Example 1. Using these pellets, a cylindrical molded article similar to that in Example 1 was obtained. In Example 2 and Comparative Examples 1 to 4, the cylinder temperature of the twin-screw extruder and the set temperature of the injection molding machine were set to the same temperatures as in Example 1, while in Examples 3 and 4 and Comparative Examples 5 to 8, the cylinder temperature of the twin-screw extruder was 220°C and the set temperature of the injection molding machine was 260°C. In addition, "PA12" in Table 1 below is polyamide 12 (product name: Grilamid L20, manufactured by M-Chemie, MVR (based on JIS K 7210, measured at a measurement temperature of 275°C and a load of 5 kg): 85 cm 3 / 10 minutes, refractive index: 1.53). The "low molecular weight PA" described in Table 1 below is Platamid 2513 (manufactured by Arkema, MVR (measured in accordance with JIS K 7210 at a measurement temperature of 180°C and a load of 2.16 kg): 24 cm 3 / 10 minutes, refractive index: 1.53). Furthermore, the "GF filler (E glass)" described in Table 1 below is a glass fiber filler made of E glass (glass chopped strands cut to a cut length of 3 mm and having a fiber diameter of φ10 μm, refractive index: 1.56, product name: ECS305K, manufactured by Chongqing International Composite Materials Co., Ltd. (CPIC)), the "GF filler (NE glass)" is a glass fiber filler made of NE glass (glass chopped strands cut to a cut length of 3 mm and having a fiber diameter of φ11 μm, refractive index: 1.51, product name: New glass, manufactured by Nittobo), and the "GF filler (D glass)" is, as described above, a glass fiber filler made of D glass (glass chopped strands cut to a cut length of 3 mm and having a fiber diameter of φ10 μm, refractive index: 1.48, product name: ECS (HL) -301TDS, manufactured by Chongqing International Composite Materials Co., Ltd. (CPIC)).

[0048] The pellets and cylindrical molded bodies obtained as described above were evaluated for their properties according to the following criteria, and the results are shown in Table 1 below.

[0049] <Connector strength> The center of each cylindrical molded body (center in the length direction) was fixed, and a JIS K 7171 indenter (tip R2.0) was pressed perpendicular to the axis into the opening at the tip of the cylindrical molded body in a cantilever state with a length of 10 mm at a pressing speed of 5 mm / min. The breaking strength (N) was measured by compression evaluation using a Strograph tensile tester. In the present invention, the breaking strength is usually required to be 450 N or more.

[0050] <Welding strength> Either resin tube A or B prepared as described below (which resin tube A or B was used is shown in Tables 1 and 2 below) was inserted 1.5 cm into the open edge of each cylindrical molded body, and while in this state, a 1060 nm laser beam was irradiated from the outside of the cylindrical molded body at a position 10 mm from the position where the tube and connector began to overlap, with a laser output of 40 W and 1 second / cycle, to weld the interface between the cylindrical molded body and the resin tube (see Figure 1). The weld strength (N) of the samples welded as described above was measured by axial tensile evaluation using a Strograph tensile tester, and evaluated according to the following criteria. Welding strength 450N or more 〇 Welding strength less than 450N ×

[0051] The resin tubes A and B were produced as follows.

[0052] [Preparation of resin tube A] 100 parts by weight of polypropylene (product name: Novatec PP BC6C, manufactured by Japan Polypropylene Co., Ltd.) and 0.1 parts by weight of carbon black (product name: MCF♯45, manufactured by Mitsubishi Chemical Co., Ltd.) were blended and melt-kneaded at a cylinder temperature of 180°C using a twin-screw extruder (screw diameter 30 nm) to obtain pellets. The pellets were then melt extruded at a set temperature of 180° C. in a melt extruder to produce a resin tube A having an outer diameter of 8 mm and a wall thickness of 1.5 mm.

[0053] [Preparation of resin tube B] 100 parts by weight of polyamide 12 (product name: Grilamid L25, manufactured by M-Chemical Corporation) and 0.1 parts by weight of carbon black (product name: MCF♯45, manufactured by Mitsubishi Chemical Corporation) were blended and melt-kneaded at a cylinder temperature of 220°C using a twin-screw extruder (screw diameter 30 nm) to obtain pellets. The pellets were then melt extruded at a set temperature of 220° C. in a melt extruder to produce a resin tube B having an outer diameter of 8 mm and a wall thickness of 1.5 mm.

[0054] <Total laser transmittance> The pellets, which were the material for each cylindrical molded body, were injection molded (injected in one direction) into a mold for a sheet-like molded body at a set temperature of 260° C. using an injection molding machine to produce a sheet with a thickness of 2 mm. The total light transmittance of the above-mentioned sheet at 1060 nm was measured using a spectrophotometer (manufactured by JASCO Corporation, V-770) and evaluated according to the following criteria. Total light transmittance 55% or more 〇 Total light transmittance less than 55% ×

[0055] <Total laser transmittance (weld evaluation)> During injection molding into the die for the sheet-like molded product, injection was performed from two opposing directions to intentionally create welds, producing a 2 mm thick sheet (for weld evaluation). The total light transmittance of the welds of the sheet was measured at 1060 nm using a spectrophotometer (JASCO Corporation, V-770) and evaluated according to the following criteria. Total light transmittance 50% or more 〇 Total light transmittance less than 50% ×

[0056] [Table 1]

[0057] From the results in Table 1 above, in Examples 1 to 4, the difference in refractive index between the base polymer (polypropylene or PA12) and the GF filler in the material of the cylindrical molded body (connector) was small (within 0.02), satisfying the requirements of the present invention, resulting in high connector strength and high total laser transmittance, and even when a weld was formed, the total laser transmittance was high. Furthermore, when the cylindrical molded body was laser welded to a resin tube, excellent weld strength was obtained.

[0058] In contrast, in Comparative Examples 1, 2, 5, and 6, the difference in refractive index between the base polymer (polypropylene or PA12) and the GF filler in the material of the cylindrical molded body (connector) was large, resulting in a low total laser transmittance and a low welding strength. In Comparative Examples 3 and 7, the amount of compatibilizer (acid-modified polypropylene or low molecular weight PA) added was large, resulting in a low total laser transmittance. In Comparative Examples 4 and 8, the material of the cylindrical molded body (connector) did not contain anything equivalent to a "compatibilizer having the same structural unit as the main chain of the base polymer and having a functional group that is reactive to the hydroxyl group on the surface of the GF filler," so the problem of aggregation of the GF filler during injection molding was not resolved, resulting in a decrease in total laser transmittance and a decrease in welding strength. [Industrial Applicability]

[0059] The resin composition for a cylindrical molded body for laser welding of the present invention can reduce the aggregation of glass fiber filler at the welds that occur significantly when injection molding a cylindrical molded body such as a connector for an automobile tube, and can improve the weldability when the cylindrical molded body is laser welded. The cylindrical molded body can be applied to connectors for automobile tubes as well as connectors for water pipes. The object to be welded to the cylindrical molded body can be applied to resin tubes, etc. [Explanation of symbols]

[0060] 1 Connector 2 Plastic tube 1a Opening edge

Claims

1. The resin composition for use in a tubular molding for laser welding contains the following components (B) and (C) together with a base polymer consisting of the following component (A), wherein the content of component (A) is 45% by weight or more based on the total of components (A) to (C) and 45% by weight or more of the entire resin composition, the content of component (B) is 10 to 50% by weight based on the total of components (A) to (C), and the weight ratio of components (B) and (C) is (B):(C)=2:0.01 to 2:

1. (A) At least one selected from the group consisting of polypropylene and polyamide (excluding (C)). (B) A glass fiber filler having a refractive index that differs from that of (A) by 0.02 or less. (C) A compatibilizer having the same structural unit as the main chain of (A) and having a functional group that is reactive to a hydroxyl group on the surface of the glass fiber filler of (B).

2. 2. The resin composition for use in a cylindrical molding for laser welding according to claim 1, wherein the component (A) is polypropylene, and the component (C) is maleic anhydride-modified polypropylene.

3. 3. The resin composition for use in a cylindrical molding for laser welding according to claim 2, wherein the maleic anhydride-modified polypropylene has a maleic anhydride modification rate of 0.1 to 4.0 mol %.

4. The component (A) is a polyamide, and the component (C) has a melt volume rate (MVR) of 1 to 200 cm3 measured at a measurement temperature of 180°C and a load of 2.16 kg. 3 2. The resin composition for use in a cylindrical molding for laser welding according to claim 1, which is a polyamide having a viscosity of 10 / 10 minutes.

5. A cylindrical molded body for laser welding, comprising the resin composition for a cylindrical molded body for laser welding according to any one of claims 1 to 4.

6. 6. The cylindrical molded article for laser welding according to claim 5, which is a connector for tubes in automobiles.

7. 7. A cylindrical molding-tube joint structure, characterized in that an end of a resin tube is inserted into the open end edge of the cylindrical molding for laser welding according to claim 5 or 6 and then laser-welded thereto.

Citation Information

Patent Citations

  • Method for joining resin molded body

    JP2005001350A

  • Composite molded product

    JP2007168163A

  • Thermoplastic resin composition for laser welding, molded article and method for producing molded article

    JP2009040808A

  • Thermoplastic resin composition for laser welding, molding, method of manufacturing molding

    JP2013053316A

  • Polyamide resin composition, kit, process for producing molded article, and molded article

    WO2017110372A1